Perkembangan Motif Flora Pada Produk Fashion Dimasa Pandemi Covid-19 - Nadia Febriani Zahara (Jurusan Seni Rupa ISBI Bandung, 2023)
The trend comes from the absorption word Trend which means the direction of a trend or style that is developing or changing in general. Trends in the fashion world are constantly changing and these changes are influenced by many factors, one of which is the social and economic conditions at that time. The Covid-19 pandemic requires everyone to adapt to the new normal (new normal era), including trends in the world of fashion. The fashion trends referred to include: 1) Fashion trends that are popularly worn; 2) complementary trends in popular clothing worn; and 3) the popular trend of accessories used during the Covid-19 pandemic era. This research method uses literary and phenomenological methods, the literary method is a type of qualitative research method where the location and place of research are carried out in libraries, documents, archives, and other similar methods with literature reviews, while the phenomenological approach seeks to capture various problems that exist in society and reveal the meaning contained therein. The results of this study are that there are various changes in dress styles in the new normal era. These changes in dress style include: 1) Fashion trends in the new normal era include minimalist clothing, sports clothing and closed clothing; 2) complementary clothing trends in the new normal era include masks, face shields, backpacks and oversized bags, flatshoes, slip ons, and sneakers; and 3) accessory trends during the new normal era, namely glasses and watches. Keywords: floral motifs, fashion products, pandemic, fashion trends ——————————————————————— Tren berasal dari kata serapan Trend yang berarti adalah arah kecenderungan atau gaya yang sedang berkembang atau berubah secara umum. Tren pada dunia fashion terus berubah dan perubahan tersebut dipengaruhi oleh banyak faktor, salah satunya adalah keadaan sosial dan ekonomi pada saat itu. Pandemi Covid-19 mengharuskan setiap orang untuk beradaptasi dengan tatanan normal baru (era new normal), termasuk tren dalam dunia fesyen. Tren fesyen yang dimaksud meliputi: 1) Tren busana yang popular dikenakan; 2) tren pelengkap busana yang popular dikenakan; dan 3) tren aksoris yang popular di gunakan selama era pandemi Covid-19. Metode penelitian ini menggunakan metode kepustakaan dan fenomologi, metode kepustakaan adalah satu jenis metode penelitian kualitatif yang lokasi dan tempat penelitiannya dilakukan di pustaka, dokumen, arsip, dan lain sejenisnya dengan literatur review, sedangkan pendekatan fenomenologi berupaya untuk menangkap berbagai persoalan yang ada di masyarakat dan mengungkap makna yang terkandung di dalamnya. Hasil penelitian ini adalah terdapat berbagai perubahan gaya berbusana di era new normal. Perubahan gaya berbusana ini meliputi: 1) Tren busana di era new normal meliputi busana minimalis, busana sport, dan busana tertutup; 2) tren pelengkap busana di era new normal meliputi masker, face shield, tas ransel dan oversized, flatshoes, slip on ,dan sneaker ;dan 3) tren aksesoris selama era new normal yaitu kacamata, dan arloji. Kata Kunci: motif flora, produk fashion, pandemi, tren fashion.